Cucurbit[8]uril-derived porous carbon as high-performance electrode material for ionic liquid-based supercapacitor. (June 2021) - Zhu, Tingting; Song, Zeyu; Lin, Jianming; Wang, Yonglan; Sun, Sijia; Fan, Leqing; Lin, Jeng-Yu; Wu, Jihuai
Highlight: Porous carbon electrode is derived from a novel macrocycle molecule cucurbit[8]uril. Cucurbit[8]uril-carbon electrode has ideal pore size of 0.88 nm and large surface area. Ionic liquid PMIMBF4 has ion diameter of 0.87 nm and potential window of 3.8 V. Supercapacitor with PMIMBF4 and cucurbit[8]uril-carbon gives high specific energy. Abstract: The porosity and electrochemical properties of electrodes play an important role in improving the specific energy of supercapacitors. In this work, a novel macrocycle molecule cucurbit[8]uril (CB8) with cavity diameter of 0.88 nm is synthesized to fabricate the porous carbon electrodes. By monomer synthesis, macromolecule cyclization, octa-cycle purification, and carbonization at 800 °C, the prepared cucurbit[8]uril-carbon (CB8C-800) material has ideal pore size distribution centered at 0.88 nm and high specific surface area of 781.51 m 2 ·g −1 . Symmetric supercapacitor device is assembled by using the CB8C-800 electrode and 1-propyl-3-methylimidazole tetrafluoroborate (PMIMBF4 ) ionic liquid electrolyte with ion diameter of 0.87 nm and wide potential window of 3.8 V. The optimized device achieves a high specific energy of 66.04 Wh·kg −1, along with a satisfactory cycling stability (90.3% capacitance retention after 10, 000 consecutive cycle). The results demonstrate an effective porous carbon material derived from cucurbituril for high specific energy supercapacitors.